Heavy metals in fishes from Sarawak River - Nur Hanisah, binti Mohd Yusof (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The main sources of heavy metals are derived from human activities such as urbanization which includes industrial and agricultural wastewater. There are also increasing of industrial development along the Sarawak River which probably increase the heavy metals accumulation in the fishes. This study was done to determine the level of heavy metals (Zn, Cu, Cd, Pb and Hg) in Hemibagrus sabanus, Hemibagrus planiceps, Osphronemus goramy, Tilapia sp., Channa micropeltes, and Scatophagus argus from Sarawak River. Fish samples (flesh, liver and gills) were digested with concentrated HNO3 (63%) and HCl (37%) on the hot plate and heavy metals concentration in fish samples were analysed by using Flame Atomic Absorption Spectrophotometer (FAAS) for Zn, Cu, Cd and Pb while Hg was analysed by using Flow Injection Mercury System (FIMS). The accumulation was observed in three parts of fish which were flesh, gills and liver in order liver > gill > flesh. The result revealed that Zn concentration was the highest in Hemibagrus sabanus (88.8 - 368.25 mg/kg), followed by Cu in Channa micropeltes (BDL - 173.08 mg/kg), Cd concentration in Tilapia sp. (6.8 - 13.38 mg/kg), Pb in Hemibagrus sabanus (0.37 - 4.09 mg/kg) and Hg concentration in Channa micropeltes (0.32 - 1.97 mg/kg). This study also found that heavy metals accumulation in Hemibagrus sabanus, Hemibagrus planiceps, Tilapia sp. and Channa micropeltes were exceeded the permissible limit recommended by FAO/WHO (1985) and not advisable for regular consumption.